Breaking Boundaries: The Real Lives of Alternative Learning System Facilitators - Cheryl P. Daga-as; Jose Antonio A. Guntalidad (Journal of Educational Management and Strategy, 2025)
This study explores the lived experiences of seven Alternative Learning System (ALS) facilitators in Tacurong City, highlighting their unwavering dedication and passion for empowering marginalized learners. The research aims to understand how facilitators sustain their commitment amid challenges such as low literacy levels, behavioral difficulties, and limited family support among learners. Using a qualitative descriptive approach, data were collected through in-depth interviews guided by 16 semi-structured questions that encouraged the facilitators to reflect on their professional journeys. The analysis revealed several key themes, including student diversity, scarcity of learning resources, facilitator resilience, emotional attachment to learners, and the significance of collaboration within the community. Despite facing limited funding, low compensation, and minimal career development opportunities, the facilitators demonstrated creativity and adaptability through the use of project-based, cooperative, and experiential learning methods. Their work was driven by personal motivation and a deep sense of purpose, enabling them to create supportive networks that promote learner success. The findings underscore the essential role of ALS facilitators in advancing inclusive education and bridging learning gaps among marginalized groups. The study recommends that the Department of Education (DepEd) strengthen the ALS program by providing greater institutional support, improved funding, and professional development opportunities for facilitators. This research contributes valuable insights for policymakers and educators seeking to enhance the sustainability and effectiveness of alternative education systems.